Langkah Inovatif Mengurangi Limbah Rumah Tangga: Sosialisasi dan Pelatihan Daur Ulang Minyak Jelantah Menjadi Lilin Aromaterapi di Desa Pudak Kec. Kumpeh Ulu Kab.Muaro Jambi : Pengabdian - Syarifah Syamilah; Sitti Aminah; Nasa Khairina; Andi Saputra; Shinta Shinta; Rendi Febriyansyah; Hendra Tera (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Community service with an innovative concept of reducing household waste by recycling used cooking oil into aromatherapy candles involving the mothers of Hamlet 2, Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency was carried out on November 14, 2025. This study examined the application of used cooking oil as the main raw material in the production of aromatherapy candles in Pudak Village, Hamlet 2. The study aims to address environmental problems caused by improperly managed used cooking oil disposal, by converting the waste into products with economic value. The production process includes filtering and refining used cooking oil, melting it with natural wax, mixing it with essential oils, and molding it into usable aromatherapy candles. The village community was actively involved through training and increasing environmental awareness, so that they were able to manage waste and at the same time open up sustainable creative business opportunities. The resulting aromatherapy candles showed good physical qualities, such as texture and burning power, and provided social and economic benefits to the local community. This initiative is a practical model of integrated waste management with community empowerment and economic development in rural areas, which is in line with the principles of environmental sustainability and improving welfare.